2011
DOI: 10.1007/s13204-011-0045-9
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide nanostructures modified multifunctional cotton fabrics

Abstract: Surface modification of cotton fabrics using graphene oxide (GO) nanostructures was reported. Scanning electron microscopic (SEM) investigations revealed that the GO nanostructure was coated onto the cotton fabric. The molecular level interaction between the graphene oxide and the cotton fabric is studied in detail using the Fourier transform infra-red (FTIR) spectra. Thermogravimetric analysis (TGA) showed that GO loaded cotton fabrics have enhanced thermal stability compared to the bare cotton fabrics. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 23 publications
1
54
0
1
Order By: Relevance
“…In Fig. 1 (curve 2), the peak at 1054 cm -1 referred to aliphatic stretching of (C-O), the peak at 1161 cm -1 referred to stretching ether system (C-O-C), the peak at 1601 cm -1 referred to stretching conjugation system (C=C-C), the peak at 1725 cm -1 referred to carbonyl group (C=O), the peak at 2918 cm -1 referred to bending and stretching of methylene group (-CH 2 -) and broad band at 3340 cm -1 are attributed to vibration of a hydroxyl group (O-H) [2,24]. The FTIR observed that the oxidation process was successfully occurred, a new groups as hydroxyl, carboxyl and epoxy have been introduced into the graphene layers.…”
Section: Ftir Characterizationmentioning
confidence: 99%
“…In Fig. 1 (curve 2), the peak at 1054 cm -1 referred to aliphatic stretching of (C-O), the peak at 1161 cm -1 referred to stretching ether system (C-O-C), the peak at 1601 cm -1 referred to stretching conjugation system (C=C-C), the peak at 1725 cm -1 referred to carbonyl group (C=O), the peak at 2918 cm -1 referred to bending and stretching of methylene group (-CH 2 -) and broad band at 3340 cm -1 are attributed to vibration of a hydroxyl group (O-H) [2,24]. The FTIR observed that the oxidation process was successfully occurred, a new groups as hydroxyl, carboxyl and epoxy have been introduced into the graphene layers.…”
Section: Ftir Characterizationmentioning
confidence: 99%
“…Once the fabric is coated with GO, it is then reduced to RGO using reducing agents such as sodium hydrosulfite [16], hydrazine [17], etc. GO coated fabrics have also generated interest due to the photo-catalytic activity of GO and also to its antibacterial activity [18]. Directly coated graphene fabrics have also been obtained in other works referenced in the bibliography [15].…”
Section: Introductionmentioning
confidence: 99%
“…Krishnamoorthy et al [55] coated cotton fabrics with GO to obtain photocatalytic and antibacterial fabrics. Photocatalytic activity was measured by measuring the photoreduction of resazurin (blue) to resorufin (pink) under UV irradiation.…”
Section: Photocatalytic Fabrics Antibacterial and Antifungal Fabricsmentioning
confidence: 99%